Gifted with Disabilities The Twice-Exceptional in India - Kurup, Anitha; Dixit, Shalini (INDIAN EDUCATIONAL REVIEW, 2016)
The ‘twice-exceptional’ is a segment of the population in whom extraordinary abilities coexist with disabilities. For a country like India with a large and diverse population of over 1.3 billion, which constitute about 10–15 percent of the gifted population, the twice exceptional children are estimated to be about 1.2 million in the age group of 3–18 years. The number of children in this specialised group is large; identifying them and providing them with appropriate services needs attention. The twice-exceptional child will need a unique environment that will simultaneously harness his/her gifts and also provide support to overcome the challenges whether theyare learning difficulties, developmental disorders, or handicaps of a perceptual, physical, or psychological nature. In the absence of any initiative for the twice-exceptional children in India, the paper discusses the need for recognition of this invisible population. Drawing from the experiences of other countries, the paper provides a framework for identification and interventions that India can undertake to address the needs of our twice-exceptional children. The paper concludes with the possible policy directions in tracing this unique population in India.